Development of morphine-induced tolerance and withdrawal: involvement of the clock gene mPer2 - Perreau-Lenz, Stéphanie; Sanchis-Segura, Carles; Leonardi-Essmann, Fernando; Schneider, Miriam; Spanagel, Rainer (European neuropsychopharmacology, 2010)
The present study has been designed to assess specifically the involvement of the clock gene mPer2 in morphine-induced tolerance and withdrawal. At first, we checked the absence of initial differences in the expression of several gene transcripts involved in the development of morphine dependence in Per2Brdm1 mutant mice and in their respective wild-type (WT) control littermates. Morphine-induced tolerance as well as precipitated withdrawal was then assessed in these mice. The Per2Brdm1 mutant mice clearly developed less tolerance and showed attenuated withdrawal signs compared to WT. These results show that mPER2 is involved in morphine-induced tolerance and withdrawal.
Gesehen am 28.04.2023